Design failure mode effects analysis and customer approach matrix: A case study in an automotive company - Ahmad, Mohd Akhir; Iteng, Rosman; Taib, Che Azlan (2018)
The most recent of increasing product failure among the automotive industry has encouraged the companies to implement quality tools such as design failure mode effects analysis (DFMEA) to prevent its defects from occurring, and transferred to the customer.The aims DFMEA to satisfy customer and stakeholders.Therefore, the using quality tools in automotive company such as DFMEA of new product development and customer approach matrix (CAM) are rarely present.This study to address the case study regarding DFMEA and CAM of new product development of automotive company in Malaysia.Thus, the outcome of this case study contributes to the enhancement of quality tools such as DFMEA and CAM in the automotive sector.The methodological approach adopted in this paper is a case study at an automotive company in Malaysia.Data were gathered from various sources. The study is limited to a single case study, several parts of new model are chosen which considers of new product development of vehicles. The study revealed that the using DFMEA as quality tools and CAM have a significant impact on organizational performance in the Malaysian automotive industry.